Antibiotic Resistance in Modern World - Leyla S. Namazova-Baranova; Alexander A. Baranov (Педиатрическая фармакология)
The article brings up the topic not only vital and urgent for further development of modern medical science, but also affecting the interests of mankind as a whole and of every inhabitant of the Earth in particular: that is the irrational use of antibiotics and antibiotic resistance which rate is growing rapidly. We investigate the reasons for the epidemic of antibiotic resistance and discuss in detail all the necessary measures in order to cope with this problem. The shocking data on the almost universal irrational use of antibiotics by both medical workers and parents is provided. We demonstrate the microbiome changes that follow antibacterial drugs application resulting in the development of severe chronic pediatric diseases which cause severe disability or life-threatening conditions in children with long-term results in adult age. In conclusion, we summarize the evidence-based research in phytomedicine that present the phytopreparations as a serious alternative to antibiotics in a number of clinical settings.